Implementation of Direct Instruction Learning Model on Students' Learning Outcomes on Electron Configuration Material - Putri, Huriyah Alifia; Bahriah, Evi Sapinatul (LAVOISIER: Chemistry Education Journal, 2024)
Understanding topics in learning must be supported by interesting learning models, especially in chemistry subjects. Learning models that are by the circumstances of students will make it easier for students to receive lessons given by the teacher. This study aims to determine the improvement of student learning outcomes by applying direct instruction learning models to electron configuration material. The research method used is descriptive. This research was conducted at Nusantara Plus High School with a sample of class X. The results showed that the average score obtained was 93.10 with the highest score of 100 and the lowest score of 70. Thus it can be concluded that the direct instruction learning model on electron configuration material can improve the learning outcomes of class X students of SMA Nusantara Plus Ciputat.